Prevalence Of Hypercalcemia Of Malignancy In Patients With Solid Tumors By Measuring Ionized Calcium In Tertiary Care Hospital - Ghazanfar Abbas; Adnan Mustafa Zubairi (ziauddin University, 2024)
Background: Hypercalcemia is relatively common in patients with cancer, occurring in approximately 20 to 30 percent of cases. As ionized calcium is not routinely estimated in most of the clinical laboratories and calcium status of the patients is being assessed by estimation of total calcium. This may result in up to 30% cases to remain undetected for hypercalcemia. The diagnosis of hypercalcemia of malignancy if made early and managed properly, could reduce this debilitating complication and objective of this study was planned to find out the prevalence of hypercalcemia of malignancy in patient with solid tumors through measurement of ionized calcium. Methods: 73 patients diagnosed with solid tumors were included in the study. Informed consent was obtained and a proposed Performa included demographic data, Type, size, stage of tumor, duration of disease. Ionized calcium levels were performed for detection of hypercalcemia. All the patients included in the study were adult of more than 18 years and no one was suffering from hematological malignancy or with acid base disorders. Results: A total of 73 patients, 36 females and 37 males, with mean age of 54.47 ± 15.98 were included (range 39-90 yrs in females, 19-83 yrs in males). 16 patients were suffering from Hypercalcemia of malignancy while 57 had normal ionized calcium levels. Conclusion: Hypercalcemia of malignancy has been detected in 21.92% cases of solid tumors in our study. Further larger studies are needed to validate our data and also it is also required to find out which type of tumor is more prone to Hypercalcemia. Key Words: Hypercalcemia of malignancy, ionized calcium, solid tumors